Palestinian Independence and Religious Extremism: Using the Palestinian Issue as a Khilafah Islamiyah Propaganda Tool on Instagram - Muhammad Ikhwan; Mohammad Bachrul Falah (Westscience Press, 2024)
Israel's attack on the Gaza area has become a major human rights issue that has attracted public attention. The genocide, which began on October 7, 2023, has claimed thousands of innocent lives. All Muslims in the world sympathize with the disaster that occurred in Palestine. However, this sympathy is vulnerable to being infiltrated by religious radicalism movements, especially those related to opinions spread on social media. Therefore, this research focuses on looking at these potentials. This research is empirical research using netnographic data collection by the hashtag #khilafah on Instagram. Based on this search, an account was found with the name @bultendakwahkaffah, which is an Instagram account for online bulletins spreading propaganda for the Khilafah Islamiyah movement. The propaganda spread by this account revolves around the implementation of an Islamic caliphate, which can guarantee the implementation of Palestinian independence. The form of Khilafah Islamyah as a representation of the unity of the Muslim ummah will liberate Palestine from Israeli colonialism, relying on the unity of all Muslims in the world and the implementation of Islamic law. The author also found that the account in question was affiliated with the ideologies of the Hizbut Tahrir organization, which was disbanded by the government in 2017. The Palestinian issue, which is full of humanity, really attracts the sympathy of the wider community. By hiding behind humanitarian issues, it is feared that the Islamic caliphate movement, which has long been a problem, will attract sympathy from many people on social media.